A deductive approach method for the determination of the discount rate in the assessment of special properties value [Un approccio deduttivo per la determinazione del discount rate nelle stime di immobili speciali] - Marco Locurcio; Francesco Tajani; Pierluigi Morano (Valori e Valutazioni, 2024)
With the financialization of the real estate market, the application of the income approach through the Discounted Cash Flow Analysis (DCFA) for estimating the market value has significantly increased. In this income approach method, the Discount Rate (DR) is one of the factors that decisively affects the result. Despite the several procedures proposed for the estimation of the DR and the numerous parameters considered, the valuer is generally «forced» to the use of the risk premium as a corrective that takes into account the “communis aestimatio” borrowed for the assessment of the DR. Starting from these premises, the present research attempts to replicate the ordinary behavior that leads the valuer to the determination of DR and to outline a methodology that allows estimating a reliable and objective value of DR on the bases of the factors generally taken into consideration.